Efektivitas Pengelolaan Dana Desa dalam Meningkatkan Kesejahteraan Masyarakat Desa Margamukti Pengalengan Menurut Persepektif Islam - Jihada, Zahra Aliya; Miftahudin (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Margamukti Village is one of the villages in Pangalengan District, Bandung Regency. Each village is ensured to get a grant from the Government called Dana Desa. The development of Margamukti village funds has been specific such as road repair, posyandu construction and community empowerment.The purpose of this study is to find out how the picture of the effectiveness of village fund management to improve community welfare in addition, this study also aims to see how the effectiveness of village fund management in improving community welfare in Islamic perspective. The approach in this study is qualitative with descriptive analysis methods using data collection techniques through documentation, observation and interviews.The results showed that the effectiveness of village fund management in improving the welfare of the people of Margamukti Village, Pangalengan District, Bandung Regency was generally quite effective, with a budget of Rp. 574,644,260. Preciceptively Islamically, Margamukti Village has implemented several processes in managing its village funds, by applying the five principles of maqasaid sharia.